How and why to analyze microbiota – a quick guide for clinicians: Kako in zakaj analiziramo mikrobioto – hitri vodnik za zdravnik - Horvat, Sabina; Rupnik, Maja (Acta Medico-Biotechnica, 2021)
Microbiota is defined as a microbial population inhabiting a given body part. The best known example is the gut microbiota, but oral, vaginal, and skin microbiota have also been studied extensively. Many body parts previously thought to be sterile have been shown to possess their own specific microbiota. Each microbiota plays an important role in organ functioning, in health, or in disease development. Therefore, microbiotas are widely studied in an effort to establish possible health or disease markers, or to use microbiota as potential therapeutic targets. The literature on microbiota has increased exponentially along with the development of methods used for analysis. An understanding of the basic principles and terms used in microbiota studies are therefore an important part of a clinician’s education.
Keywords: microbiota; metagenomics; next generation sequencing; personalized medicine; disease markers